2019
DOI: 10.1152/ajprenal.00333.2019
|View full text |Cite
|
Sign up to set email alerts
|

Urinary physiology and hypoxia: a pilot study of moderate-altitude trekking effects on urodynamic indexes

Abstract: Exposure to high altitude is one of the most widely used models to study the adaptive response to hypoxia in humans. However, little is known about the related effects on micturition. The present study addresses the adaptive urinary responses in four healthy adult lowlanders, comparing urodynamic indexes at Kathmandu [1,450 m above sea level (a.s.l.); K1450] and during a sojourn in Namche Bazar (3,500 m a.s.l.; NB3500). The urodynamic testing consisted of cistomanometry and bladder pressure/flow measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Since hypoxaemia, defined as a decrease in arterial oxygen tension 8 , is also a predominant feature of the high-altitude environment, research on the pathophysiologic processes behind hypoxia was significantly facilitated with the advent of altitude simulation tests 9 . On the cellular level, hypoxic stress initiates a transcriptional response by hypoxia inducible factors (HIF; during intermittent hypoxia predominately HIF-1α [10][11][12], which leads to a reduction of cellular energy consumption, a secretion of pro-angiogenic and survival factors 10 , and qualitative changes in mitochondrial function 13 , which in turn results in alterations of the cardiovascular, haematological and even urinary physiology 14,15 . Among the observed physiological alterations in response to hypoxia, the effects on the human macrocirculatory system have been subject to several extensive scientific investigations in the past.…”
Section: Llsmentioning
confidence: 99%
“…Since hypoxaemia, defined as a decrease in arterial oxygen tension 8 , is also a predominant feature of the high-altitude environment, research on the pathophysiologic processes behind hypoxia was significantly facilitated with the advent of altitude simulation tests 9 . On the cellular level, hypoxic stress initiates a transcriptional response by hypoxia inducible factors (HIF; during intermittent hypoxia predominately HIF-1α [10][11][12], which leads to a reduction of cellular energy consumption, a secretion of pro-angiogenic and survival factors 10 , and qualitative changes in mitochondrial function 13 , which in turn results in alterations of the cardiovascular, haematological and even urinary physiology 14,15 . Among the observed physiological alterations in response to hypoxia, the effects on the human macrocirculatory system have been subject to several extensive scientific investigations in the past.…”
Section: Llsmentioning
confidence: 99%
“…A growing body of evidence indicates that hypoxia decreases both the activity and effectiveness of the antioxidant system, as well as causing increased ROS production with a consequent increase in oxidative damage [ 3 ] to lipids [ 4 , 5 , 6 ], proteins and the DNA [ 5 , 7 ] of cellular compartments [ 8 , 9 , 10 ]. Most studies on the effects of hypoxia have been carried out at high altitude [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, under such conditions, several factors other than hypoxia could induce oxidative damage; UV radiation, intense physical activity and cold may in fact produce an imbalance between ROS generation and antioxidant protection [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the recent development of non-linear metrics allowed to extend the methodological rationale of HRV, e.g., Gomes and colleagues (Gomes et al, 2017 ) reported physical exercise to acutely reduce the chaotic behavior of heart rate dynamics, through the complex Higuchi Fractal Dimension (HFD) analysis. Indeed, alternative approaches to the typical HRV investigation may add novel interpretation levels to the non-uniform alterations in the several HRV domains observed in response to altitude exposure (Verratti et al, 2019 ). Dhar et al ( 2018 ) reported higher mean RR, LF (low frequency) power ms 2 , LF (normalized units: nu), and LF/HF ratio values, with lower RMSSD (root mean square of successive RR interval differences), NN50, pNN50 (percentage of successive RR intervals that differ by more than 50 ms), SD1 (Poincaré plot standard deviation perpendicular the line of identity), HF (high frequency) power ms 2 and HF (nu) values, in acclimatized lowlanders (15–18 months residence at >3,500 m asl) compared to HAs native and sea-level residents never exposed to HAs.…”
Section: Introductionmentioning
confidence: 99%